Property, Substance, and Effect Anthropological Essays on Persons and Things - Strathern, Marilyn (HAU Books, 2023)
This title draws on Strathern,Äôs interest in the reification of social relations. If the world is shrinking in terms of resources and their access, it is expanding in terms of new candidates for proprietorship. How new relations come into being is among the many questions about property, ownership, and knowledge brought together here. Twenty years have not diminished interest in the book,Äôs opening challenge: if one were inventing a method of enquiry by which to configure the complexity of social life, one might wish to invent something like the anthropologist,Äôs ethnographic practice. A wide range of studies deliberately brings into conversation claims people make on one another through relations imagined in the form of body-substance along with the increasing visibility of conceptual or intellectual work as property. Wherever one lives, categories of knowledge are being dissolved and reformed at a tempo that calls for the lateral reflection afforded through the ,Äúethnographic effect.,Äù